Rantai Nilai Kopi Robusta Pada Kelompok Tani Ngudi Rahayu XI Desa Kebondalem, Kecamatan Jambu, Kabupaten Semarang - Debra, Malinny; Wulanningrum, Hesti; Muhsoni; Suranto, Agus; Furoida, Aini Nur; Susilowati, Indah (Universitas Medan Area, 2025)
This study aims to identify and analyze the robusta coffee value chain in the Ngudi Rahayu XI Farmer Group in Kebondalem Village, Jambu District, Semarang Regency to determine the added value that can be obtained from each stage of the process in the robusta coffee supply chain and development strategies that can increase farmers' income. The research method used descriptive qualitative analysis with data collection through observation, interviews and discussions with farmers and quantitative related to added value using the hayami method. The results showed that the processing and marketing stages of robusta coffee final products generate the greatest added value. In particular, processing into dried coffee ose produces a total value-added of Rp 2,510 and packaged ground coffee of Rp 7,672 for every kilogram of wet ground coffee. Evidently that further processing to finished products generates greater value-added than selling semi-finished products. However, fluctuating coffee prices, limited access to market information, and technology are problems that coffee farmer groups still face. Therefore, to increase competition and profits for robusta coffee farmers in Kebondalem Village, it is necessary to improve the value chain through innovations in the processing process. value chain improvement through innovations in processing, implementation of integrated quality management, and implementation of effective marketing strategies.